Twenty-three woodcock in twenty-two years : reflections on hunting, the night sky, and our place in the universe - Wilkerson, Jeff, 1965- (University of Iowa Press, 2024)
"Follow the journey of one bird hunting astronomer as he seeks out a single woodcock, an enigmatic migratory bird of the uplands, to hunt and eat each autumn, reflecting on the gift that single bird is, as well as the gift of the land around and the universe beyond. Stories of how we understand the universe mesh with stories of time in the field and tales of good health and bad as life rolls forward across decades, and everything evolves around us while we expect, consciously or otherwise, for our world to remain unchanged. While our thoughts soar to the stars that produced the chemical elements that form us and all the land and its creatures, simple reflections on going afield to harvest a woodcock for a special holiday meal ground us. What emerges is a love story for a bird, the land and all of creation from atomic nuclei to the farthest reaches of the universe, and a reminder to acknowledge the gentle flow of time while cherishing the everyday existence around us"--